2021
DOI: 10.1007/s00146-021-01310-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards an effective transnational regulation of AI

Abstract: Law and the legal system through which law is effected are very powerful, yet the power of the law has always been limited by the laws of nature, upon which the law has now direct grip. Human law now faces an unprecedented challenge, the emergence of a second limit on its grip, a new “species” of intelligent agents (AI machines) that can perform cognitive tasks that until recently only humans could. What happens, as a matter of law, when another species interacts with us, can be integrated into human minds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Ethically and socially problematic uses of AI in differing contexts, as well as assessments of its risks, such as in medicine, work processes and human resource management, education, law enforcement, and more, have long been the subject of intense socio-political debates. 1 The widely shared assumption is that measures to regulate and standardize AI can reduce doubts and increase social acceptance, satisfy legal frameworks, and create legal certainty for AI applications, and moreover solve a wide range of ethical application problems (e.g., Tsamados 2022;Gervais 2023;Gill 2023;Finocchiaro 2023;Foffano et al 2023). For example, the EU Commission pointedly states that the greatest risks associated with the use of AI concern the application of rules protecting fundamental rights, including data protection and privacy and nondiscrimination, as well as security and liability issues (cf.…”
Section: Introduction: Discussion On Ai Regulationmentioning
confidence: 99%
“…Ethically and socially problematic uses of AI in differing contexts, as well as assessments of its risks, such as in medicine, work processes and human resource management, education, law enforcement, and more, have long been the subject of intense socio-political debates. 1 The widely shared assumption is that measures to regulate and standardize AI can reduce doubts and increase social acceptance, satisfy legal frameworks, and create legal certainty for AI applications, and moreover solve a wide range of ethical application problems (e.g., Tsamados 2022;Gervais 2023;Gill 2023;Finocchiaro 2023;Foffano et al 2023). For example, the EU Commission pointedly states that the greatest risks associated with the use of AI concern the application of rules protecting fundamental rights, including data protection and privacy and nondiscrimination, as well as security and liability issues (cf.…”
Section: Introduction: Discussion On Ai Regulationmentioning
confidence: 99%
“…A point of concern that has emerged regarding AI's adherence to ethical principles is that it is still in its relatively early stages of development and application (Bird et al, 2020). Another important question regarding how AI will be developed, used, and implemented in the future is whether or not the laws that currently exist can effectively regulate AI (Gervais, 2021). Furthermore, the (European Group on Ethics in Science and New Technologies Statement on Artificial Intelligence, Robotics, and Autonomous Systems, (2018) revealed that the challenge of governing AI was once limited to theoretical, technical, and academic discussions, but it has recently gained attention as governments and private businesses from geopolitical areas, such as the European Union, China, and the United States, have developed statements and policies regarding AI and ethics.…”
Section: Ai Ethicsmentioning
confidence: 99%
“…AI is becoming increasingly prevalent in our society, and as such, there are many legal and ethical challenges that arise [ 5 , 6 ]. The challenges associated with AI include fairness, effectiveness, cybersecurity, and intellectual property, among others.…”
Section: Current Regulatory Processmentioning
confidence: 99%
“…Although some advocate for general regulation [ 5 , 6 ] to apply to AI across sectors, this paper advocates for the necessity of precise regulation for health care AI. By developing regulations that are specific to the health care industry, policy makers can ensure that AI is being used in an ethical and responsible manner.…”
Section: Introductionmentioning
confidence: 99%